2023
DOI: 10.1101/2023.03.27.23287781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

(Poly)phenols in Human Breast Milk and their health benefits for the newborn

Abstract: Human breast milk is the first food source available to newborns and is responsible for healthy growth and development during the first months of life. Human breast milk contains vitamins, hormones, cytokines, microbiota, and immune cells that are responsible for such healthy conditions. Nonetheless, knowledge of the vast array of molecules present in human breast milk and their potential health effects is still lacking. The effects of mothers diets on the molecules present in human breast milk are also genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The breast milk also contained polyphenols such as flavonols, flavones, and isoflavones. Several studies have shown that polyphenols are abundant in human breast milk and they could be beneficial to the infants (Lu et al 2021, Song et al 2013, Carregosa et al 2023). In contrast, toxic xenobiotics, such as mycotoxins, were detected at a low prevalence in breast milk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The breast milk also contained polyphenols such as flavonols, flavones, and isoflavones. Several studies have shown that polyphenols are abundant in human breast milk and they could be beneficial to the infants (Lu et al 2021, Song et al 2013, Carregosa et al 2023). In contrast, toxic xenobiotics, such as mycotoxins, were detected at a low prevalence in breast milk.…”
Section: Resultsmentioning
confidence: 99%
“…The breast milk samples from this cohort were previously analyzed with a targeted LC-MS/MS workflow focusing on polyphenols (Berger et al 2024), and similar analytes and patterns were observed between both assays. Several studies have shown that polyphenols are abundant in human breast milk and they could be beneficial to infants (Lu et al 2021, Song et al 2013, Carregosa et al 2023).…”
Section: Resultsmentioning
confidence: 99%